Ulusal ve uluslararası bağlamda kent diplomasisi uygulaması : İstanbul örneği - Yavaşoğlu, Emine Büşra (My University, 2022)
Küreselleşme yaşamın birçok alanında etkin rol oynamaktadır. Bilgi teknolojileri ve iletişim ağlarının gelişmesi kentlerin görünürlüğünü arttırarak uluslararasılaşma sürecini hızlandırmıştır. Kentlerin uluslararasılaşma süreci kentlerin uluslararası aktör olarak var olmasını sağlamaktadır. Bu kapsamda kentler, belirledikleri yerel dış politika doğrultusunda kent diplomasi faaliyetleri yürütmektedir. Kent diplomasi faaliyetinin temelini oluşturan anlayışa göre kentler çıkarlarını uluslararası sistemde savunmaları kentler arası dayanışmayı, etkileşimi ve bilgi alışverişini arttırmaktadır. Bu tez çalışması İstanbul ölçeğinde yerel yönetimlerin ulusal ve uluslararası hibe/ fon kaynak kullanımını kent diplomasi çerçevesinde analiz edecektir. Bu tez çalışmasının amacı kent diplomasinin kavramsal çerçevesini oluştururken kentlerin yerel diplomasi faaliyetleri üzerinden potansiyellerini anlamak ve Büyükçekmece, Pendik ve Beşiktaş Belediyeleri ile derinlemesine mülakattan elde edilen bulgular ışığında durumlarını analiz etmektir. Yerel yönetimlere, uluslararası bir bakış açısı kazandırma konusunda belediye birliklerinin sağladığı imkanlar da önemlidir. Dolayısıyla çalışma kapsamında uluslararası sistemde etkin role sahip Birleşmiş Kentler ve Yerel Yönetimler Teşkilatı’nın (UCLG) Orta Doğu ve Batı Asya Teşkilatı (UCLG-MEWA), ulusalda Türkiye Belediyeler Birliği (TBB) ve bölgesel olarak Marmara Belediyeler Birliği (MBB) ile gerçekleştirilen görüşmeler doğrultusunda belediyelerin kent diplomasi faaliyeti kapsamında hibe/ fon kaynakları da incelenmiştir. Bu doğrultuda dış ilişkiler müdürlüklerinin/ ofislerinin birbirine bağımlı küresel bir yapıya sahip politika izleyerek, politika odaklı kent diplomasisi geliştirmelidir. Kentlerde yaşayan vatandaşlarda uluslararasılaşma süreci hakkında farkındalık oluşturarak bu sürecin onların hayatlarını zenginleştirip değiştireceği için katılımı arttırılmalıdır. Dış ilişkiler müdürlükleri/ ofisleri, ele aldıkları küresel politika alanlarının etkisine öncelik vererek ve bu durumun kentin uluslararası imajını ve etkisini nasıl değiştirdiğini anlayarak, kendi veri ihtiyaçlarını ve değerlendirme süreçlerini yönetebilirler. Dolayısıyla yerel yönetimlerin kent diplomasisini daha efektif ve stratejik kullanabilmeleri için ve ileride yerel yönetimlerin farklı kapasite geliştirme yollarına başvurulabilmesi için önerilerde bulunulmuştur.

Globalization plays an active role in many areas of life. The development of information technologies and communication networks has accelerated the internationalization process by increasing the visibility of cities. The process of internationalization of cities enables cities to exist as international actors. In this context, cities carry out urban diplomacy activities in line with the local foreign policy they have determined. According to the understanding that forms the basis of urban diplomacy activity, the defense of cities in the international system increases solidarity, interaction, and information exchange between cities. The fact that it is a concept that has just become widespread among local administrations in Turkey and the lack of Turkish resources at this point provided motivation for the thesis study. The thesis study was based on the concept of urban diplomacy and a study was made on the effect of national and international grant/ funding use on urban diplomacy. Istanbul is a metropolitan city with its economy and population, but it has been observed that local district municipalities do not have the same advantages. The aim of this thesis study is to understand the potential of cities through local diplomacy activities while creating the conceptual framework of urban diplomacy and to analyze their situation in the light of the findings obtained from in-depth interviews with Büyükçekmece, Pendik and Beşiktaş Municipalities. The opportunities provided by municipal associations are important in giving local governments an international perspective. Therefore, within the scope of the study, suggestions and recommendations were made in order for municipalities to use grant/ funding resources more effectively within the scope of urban diplomacy activities in line with the Middle East and West Asia Organization (UCLG-MEWA) of the United Cities and Local Governments Organization (UCLG), which has an active role in the international system, the Union of Municipalities of Turkey (TBB) nationally and the Union of Marmara Municipalities (MBB) regionally. In this direction, foreign relations directorates/ offices should follow a policy with an interdependent global structure and develop policy-oriented urban diplomacy. In this direction, foreign relations directorates/ offices should develop policy-oriented urban diplomacy by following a policy with an interdependent global structure. By raising awareness of the internationalization process in the citizens living in the cities, the participation of this process should be increased as it will enrich and change their lives. External relations directorates/ offices can manage their own data needs and assessment processes, prioritizing the impact of the global policy areas they address and understanding how this is changing the city's international image and impact. Therefore, suggestions have been made for local governments to use urban diplomacy more effectively and strategically and to apply different ways of capacity building of local governments in the future.
Keywords: Dış ilişkiler; Foreign relations; International Financial Resources; Kent Diplomasisi; Local government; Turkey; Türkiye; Uluslararası Mali Fon Kaynakları Local Foreign Policy; Urban Diplomacy; Yerel Dış Politika; Yerel yönetim